The Effect of Green Tea Leaf Extract on Spatial Memory Function and Superoxyde Dismutase Enzyme Activity in Mice with D-galactose Induced Dimentia - Gumay, Ainun Rahmasari; Bakri, Saekhol; Utomo, Astika Widy (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2017)
Background: Oxidative stress and inflammation play an important role in pathogenesis of brain aging and neurodegenerative diseases such as Alzheimer. Green tea has been shown to have antioxidant, anti-inflammatory, anticancer, and neuroprotective activity.Objectives: to determine the effect of green tea extract on spatial memory function and superoxide dismutase enzyme activity in mice with D-galactose induced dementiaMethods: An experimental study using